2011
DOI: 10.1158/1078-0432.ccr-11-0086
|View full text |Cite
|
Sign up to set email alerts
|

XPF Expression Correlates with Clinical Outcome in Squamous Cell Carcinoma of the Head and Neck

Abstract: Purpose Tumor-specific biomarkers that predict resistance to DNA damaging agents may improve therapeutic outcomes by guiding the selection of effective therapies and limiting morbidity related to ineffective approaches. XPF (ERCC4) is an essential component of several DNA repair pathways and XPF-deficient cells are exquisitely sensitive to DNA damaging agents. The purpose of this study was to determine whether XPF expression levels predict clinical response to DNA damaging agents in head and neck squamous cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 43 publications
(48 reference statements)
5
43
1
Order By: Relevance
“…Although no previous HNC studies examined rs3136038 or rs3136130 on ERCC4 , two studies assessed nine other ERCC4 SNPs (rs1799799, rs1799801, rs3136105, rs3136146, rs3136152, rs3136155, rs3136166, rs3136189, rs3136202), many of which were in LD with the SNPs in our study ( r 2 >0.80, CEU population) [10, 16, 33]. While five of these SNPs were not associated with progression-free survival among HNC cases, four SNPs appeared to be associated with worse progression-free survival contrary to our study [10, 16].…”
Section: Discussionmentioning
confidence: 85%
“…Although no previous HNC studies examined rs3136038 or rs3136130 on ERCC4 , two studies assessed nine other ERCC4 SNPs (rs1799799, rs1799801, rs3136105, rs3136146, rs3136152, rs3136155, rs3136166, rs3136189, rs3136202), many of which were in LD with the SNPs in our study ( r 2 >0.80, CEU population) [10, 16, 33]. While five of these SNPs were not associated with progression-free survival among HNC cases, four SNPs appeared to be associated with worse progression-free survival contrary to our study [10, 16].…”
Section: Discussionmentioning
confidence: 85%
“…Tumor hypoxia was measured non-invasively by 18 The majority of cisplatin-induced DNA adducts are repaired by the NER pathway (19,20), and the expression of the ERCC1 NER gene is associated with tumor resistance to CDDP cytotoxicity. Higher expression of ERRC1 was associated with inferior progression free survival for HNSCC after cisplatin radiotherapy (21,22), and ERCC1 expression has good prognostic value in patients with HPV-negative tumors (21). The percent of ERCC1-positive cell nuclei in viable regions of the tumor was measured after the CDDP containing regimens.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Although a few small studies have reported associations between levels of expression of proteins involved in DNA repair and survival in head and neck cancer patients (52)(53)(54), none appear to have explored the influence of smoking on these relationships.…”
Section: Other Potential Mechanismsmentioning
confidence: 99%